Analysis of automated monitoring for results-based agri-environmental schemes - Storkamp, Fredric (2020)
Results-based agri-environmental policies on the one side, and automation through technology, for instance in monitoring, on the other side, are two favored ways of the European Commission for a more effective and more cost-efficient Common Agricultural Policy. But how well do these two aspects go together? This thesis analyses transaction cost scenarios of current on-thespot controls and automated controls in a case example in a species rich grassland scheme in Baden-Württemberg (FAKT B3). Drones were identified in a literature review as a viable option for this application. Interviews with authority officials and a drone service provider were conducted to estimate the transaction costs of the different scenarios. The findings were then analyzed in a sensitivity analysis and discussed quantitatively and qualitatively. The results show that cost efficiency improvements are possible, however only in scenarios with low costs for drone flights or higher automation degrees, for now. Projections for future developments imply that automation gets financially more attractive. The biggest hurdle for greater cost savings is the fact, that many monitoring tasks of the FAKT B3 scheme are currently combined with other agri-environmental schemes. Therefore, there is a need for better harmonization, if automatic monitoring technologies are to be implemented, between schemes to benefit from economies of scope.